An analogue study investigating voice-hearing following exposure to stressful material. Issue 1 (2nd January 2018) - Wong, Samantha; Bucci, Sandra; Huque, Akib Ul; Hartley, Samantha; Brown, Richard J.; Berry, Katherine
Abstract: Non-clinical participants viewed pictures of either neutral or stressful interpersonal scenes before completing a voice-detection task. Exposure to stress did not influence voice detection, but scores on a measure of depersonalisation were positively correlated with voices.